Applying Modern Digital Technologies to Process and Analyze Ancient Historical Maps of Iraq: A study in Contemporary Geographical Thought - Obaid, Mohammed Fezaa (Journal of Tikrit University for Humanities, 2024)
The importance of this study is highlighted in reviewing the sources that dealt with historical maps imported from reliable websites, with the aim of making ideal improvements to them and increasing the clarity and quality of the image for the purpose of analyzing them, especially in the field of evaluating their geometric accuracy after inserting them into specialized software environments, using artificial intelligence in the geographic information systems program and benefiting from it in processing the studied historical maps. Hence, the importance of this research emerged with the aim of increasing accuracy and clarity by doubling the number of pixels and improving their quality. The study concluded that the ideal resolution for the clarity of images of historical maps for the purpose of analysis is between (300 - 1200) pixels per inch.